2016
DOI: 10.1080/00221325.2016.1148659
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and Depression in Children: The Role of Cognitive Emotion Regulation Strategies

Abstract: This study's general objective was to analyze whether different types of cognitive emotion regulation strategies (CERS), namely adaptive strategies-specifically positive refocusing and positive reappraisal-and maladaptive strategies-self-blame, catastrophizing, and rumination-mediated the neuroticism-depression relationship in children 9-12 years old, and whether gender and school transition moderated the relationships proposed. A self-reporting measure was administered to 315 children to evaluate said variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 81 publications
(119 reference statements)
5
31
0
8
Order By: Relevance
“…However, investigations of shame have normally been centered around separating from guilt [17] but some studies have shown that these three mediators are distinct [13]. Furthermore, cognitive flexibility, shame and emotion dysregulation have been involved in various types of psychopathology such as bipolar disorder and borderline personality disorder [18], anxiety [13] bulimic symptoms [19], and alcohol and drug abuse [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations of shame have normally been centered around separating from guilt [17] but some studies have shown that these three mediators are distinct [13]. Furthermore, cognitive flexibility, shame and emotion dysregulation have been involved in various types of psychopathology such as bipolar disorder and borderline personality disorder [18], anxiety [13] bulimic symptoms [19], and alcohol and drug abuse [9].…”
Section: Introductionmentioning
confidence: 99%
“…En conclusión, se puede afirmar que la estructura interna del CERQ-18 respaldada por el modelo teórico de Medrano et al (2016) es un instrumento con adecuadas propiedades psicométricas que posibilitaría una caracterización más precisa de los grupos evaluados. Del mismo modo, debido a su extensión es posible utilizarlo en estudios más complejos que busquen analizar, desde un marco explicativo, los antecedentes y consecuentes de los dos conjuntos de estrategias analizadas, tanto a nivel personal, familiar, social y académico, a modo de replicación de lo hallado en otros contextos latinoamericanos (Andrés et al, 2016). Con todo, dados los indicadores de confiabilidad, no se recomienda su uso para toma de decisiones a nivel individual.…”
Section: Discussionunclassified
“…M1: El modelo original de nueve factores oblicuos (Garnefski et al, 2001). M2: El modelo propuesto por Andrés y colaboradores (Andrés et al, 2016) en donde las estrategias automáticas presenta un modelo bifactor en el cual existe un FG y factores específicos ortogonales que involucran a las estrategias de autoculparse, rumiación, catastrofización; mientras que las estrategias elaborativas se agrupan sobre la base de un modelo de cuatro factores oblicuos (aceptación, poner en perspectiva, reinterpretación positiva, y focalización en los planes). En cada uno de los modelos se evaluó la normalidad multivariada mediante el coeficiente de Mardia, donde valores superiores a 70 indican un alejamiento de dicha distribución (Rodríguez & Ruiz, 2008).…”
Section: Análisis De Datosunclassified
See 1 more Smart Citation
“…First we present the problem of interaction between negative affects (emotional instability, anger state and trait, physical and verbal aggression and depression) analyzing the different relationship through the time in our sample. The second goal will be to contribute to the managing of the negative affections depending on their relation to other elements (14) and this way to be able to delineate the most effective protection when facing this type of alterations (15). …”
Section: Introductionmentioning
confidence: 99%